Zuckerrohr und Zuckerrübe im subtropischen Trockengürtel der Alten Welt - Blume, Helmut (ERDKUNDE, 1967)
After a presentation of the spread of sugar-cane cultivation in the dry belt of the Old World (Indus Plain, Khusistan, the Levant, Egypt, Morocco, Andalusia, Sicily) by the Arabs during the Middle Ages (Part I) follows the presentation of the spatial concentration of sugar-cane planting in recent times as a follow-on to cane sugar production in the Tropics (Part II) and then a short sketch of the contemporary extent of planted land devoted to sugar-cane and sugar-beet (Part III). The main part of the investigation lies in Parts IV and V, in which all areas of current sugar production are com paratively described with reference to climatic conditions and factors of agricultural geography. In Part IV we have the areas of one-sided sugar-cane plantings (Indus Plain in Pakistan, Egypt, Khusistan, Irak) and those of one-sided sugar-beet cultivation (Spain, the Levant, Iran). In Part V we have the areas where both cane and beet are grown (Costa del Sol of Andalusia, Peshawar Basin). Despite all attempts to increase plantings of sugar-cane and beet, the subtropical dry belt assumes only a subordinate position in world production. Within it we have the Polar boundary of the sugar cane and the Equatorial boundary of the sugar beet. The combination of the cultivation of both these crops, which is possible in some parts of the sub-tropical dry belt, seems best suited to the climatic transition regions between the Tropics and particular lines of latitude, where it can minimise harvest risks and increase the economic strength of sugar production.